Realisation of Socio-Economic Justice through the Directive Principles of State Policy: An Analytical Study of Article 38 and Article 39 of the Constitution of India - Babu Singh Rattan, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The Directive Principles of State Policy embodied in Part IV of the Constitution of India reflect the constitutional vision of establishing a just social order grounded in equality, welfare, and socio-economic justice. Among these, Article 38 and Article 39 occupy a central position as they collectively mandate the State to promote the welfare of the people, minimize inequalities, and ensure equitable distribution of material resources to subserve the common good. This paper undertakes an analytical study of the role of Articles 38 and 39 in realizing socio-economic justice, examining their constitutional philosophy, scope, and relevance in the contemporary Indian context. The study explores how these provisions guide legislative and executive action in addressing issues such as economic disparity, concentration of wealth, livelihood security, and social welfare. It critically evaluates judicial interpretations and policy initiatives that have sought to operationalize these Directive Principles, highlighting both achievements and limitations in their implementation. By situating Articles 38 and 39 within the broader framework of constitutional governance, the paper emphasizes their transformative potential in shaping an inclusive and equitable socio-economic order. The analysis underscores that although the Directive Principles are non-justiciable, they serve as essential instruments of moral obligation and policy direction, reinforcing the commitment of the Indian State to social and economic justice in a democratic society.
Keywords: Socio-economic justice; Directive Principles of State Policy; Article 38; Article 39; Constitution of India; welfare state; distributive justice; constitutional governance